2019
DOI: 10.1097/pai.0000000000000687
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma-associated Fibroblasts are a Common Finding in the Microenvironment of HPV-positive Oropharyngeal Squamous Cell Carcinoma

Abstract: The important role of the human papillomavirus (HPV) is widely established in oropharyngeal squamous cell carcinoma (OPSCC). The behavior of a OPSCCs especially induced by HPV might be influenced by the tissue microenvironment and its changes according to the tumor nature. Recognition of the role of the tumor microenvironment on the behavior of neoplastic cells has led to utilization of the microenvironment to use as therapeutic target. Carcinoma-associated fibroblasts (CAFs), the most abundant cells in the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The lower percentage of connective tissue cells in tumor cell clusters of patients with HPV + OPSCC (Table 5 ) may be associated with a lower fibroblast response compared to patients with HPV-OPSCC. This observed “desmoplastic reaction” supports cancer migration and invasion in vitro, as reported by Bolt [ 9 ] and Rahrotaban [ 37 ]. In contrast, a higher percentage of connective tissue cells was identified in the stroma of HPV + compared to HPV- OPSCC samples (Table 5 ), as described by Mohamed and coauthors [ 38 ].…”
Section: Discussionsupporting
confidence: 86%
“…The lower percentage of connective tissue cells in tumor cell clusters of patients with HPV + OPSCC (Table 5 ) may be associated with a lower fibroblast response compared to patients with HPV-OPSCC. This observed “desmoplastic reaction” supports cancer migration and invasion in vitro, as reported by Bolt [ 9 ] and Rahrotaban [ 37 ]. In contrast, a higher percentage of connective tissue cells was identified in the stroma of HPV + compared to HPV- OPSCC samples (Table 5 ), as described by Mohamed and coauthors [ 38 ].…”
Section: Discussionsupporting
confidence: 86%
“…The role of fibroblasts in the tumour microenvironment of OPSCC has been understudied, even when compared to those at other sites within the head and neck. Others have shown that CAFs are frequently identified in the TME of HPV+ OPSCC (23), but, in general, the data (IHC and sequencing) suggests higher fibroblast signatures in HPV-negative OPSCC when compared with HPV-positive OPSCC (18). The data which we have generated from the assessment of the OPSCC TMAs would bear this out (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…The ECM is produced by multiple TME cell types and weaves an intricate fiber network not only providing structural support but also regulating the physical and biochemical properties of the tumor microenvironment, thereby regulating the polarity, migration and signaling of cancer cells [24]. The tumor microenvironment not only plays a key role in tumor progression but also is associated with chemoresistance [25,26]. In breast cancer, attachment of malignant cells to the ECM alters their polarization and causes resistance to etoposide-induced apoptosis [27].…”
Section: Discussionmentioning
confidence: 99%